Central bank digital currency: Motivations and implications - Walter Engert; Ben Siu-Cheong Fung (Bank of Canada, 2017)
The emergence of digital currencies such as Bitcoin and the underlying blockchain and distribution ledger technology have attracted significant attention. These developments have raised the possibility of considerable impacts on the financial system and perhaps the wider economy. This paper addresses the question of whether a central bank should issue digital currency that could be used by the general public. It begins by discussing the possible motivations for a central bank to issue a digital currency. The paper then sets out a benchmark central bank digital currency (CBDC) with features that are similar to cash. The implications of such a digital currency are explored, focusing on central bank seigniorage, monetary policy, the banking system and financial stability, and payments. Finally, a CBDC that differs from the benchmark digital currency in a significant way is considered.
Keywords: E; E4; E41; E42; E5; 330; Bank notes; Digital currencies; Financial services; Payment clearing and settlement services